Dapatkah Identitas Keibuan Dikonstruksi Melalui Komodifikasi di Media Sosial? - Maria Febiana Christanti; Anwar Ilmar (Society, 2025)
This article presents insights into the commodification that constructs identity. The researcher focuses on mothers who have become micro-celebrities on social media. While maternal identity was previously confined to private or domestic spaces, mothers now appear as content creators. This reflects a process of commodification that transforms maternal experiences into commercial value. The commodification process of mothers involves identity reconstruction that integrates maternal values with the business dynamics of the digital era. The resulting content not only builds emotional closeness with the audience but also shapes a new paradigm in the social representation of mothers. Using a qualitative approach, this study explores how social media commodification shapes the dynamics of cultural norms, national identity, and traditional values. The result reveals that motherhood identity has undergone negotiation among mothers, the social environment, and the social media market to reach a mutually beneficial meeting point. The results also open the door to critical discussion of the impact of technology on the construction of identity and traditional values. It also provides in-depth insights into identity shifts amidst the flow of digitalization. Thus, this article contributes to an interdisciplinary understanding of the commodification and identity of mothers in social media spaces.